NATIONWIDE ASSESSMENT OF MORTALITY DISPARITIES LINKED TO ACUTE MYOCARDIAL INFARCTION AND COVID-19 IN THE US - Amer Muhyieddeen; Sachini Ranasinghe, MD; Susan Cheng, MD; Mamas A Mamas, BM BCh; Dorian Beasley, MD; Galen Cook Weins, MS; Martha Gulati, MD MS (Elsevier, 2023)
Therapeutic Area: ASCVD/CVD in Special Populations Background: The influence of the COVID-19 pandemic on possible racial disparities in the management and outcomes of acute myocardial infarction (AMI) remains uncertain. We investigated the management and outcomes of AMI patients during the first nine months of the pandemic, comparing cases with and without COVID-19. Methods: We identified all patients hospitalized for AMI in 2020 using the National Inpatient Sample (NIS), identifying those with or without concurrent COVID-19. Logistic and linear regression was used for analyses of associations, with adjustment for potential confounders. Results: Patients with both AMI and COVID-19 experienced higher in-hospital mortality rates (aOR 3.19, 95% CI 2.63-3.88), increased mechanical ventilation usage (aOR 1.90, 95% CI 1.54-2.33), and more frequent hemodialysis (aOR 1.38, 95% CI 1.05-1.89) compared to those without COVID-19 (Figure 1). Black and Asian/Pacific Islander patients faced higher in-hospital mortality than White patients, with aORs of 2.13 (95% CI 1.35-3.59) and 3.41 (95% CI 1.5-8.37), respectively. Furthermore, Black, Hispanic, and Asian/Pacific Islander patients demonstrated higher odds of initiating hemodialysis, with aORs of 5.48 (95% CI 2.13-14.1), 2.99 (95% CI 1.13-7.97), and 7.84 (95% CI 1.55-39.5), respectively, and were less likely to receive PCI for AMI, with aORs of 0.71 (95% CI 0.67-0.74), 0.81 (95% CI 0.77-0.86), and 0.82 (95% CI 0.75-0.90), respectively. Additionally, Black patients were less likely to undergo CABG surgery for AMI (aOR 0.55, 95% CI 0.49-0.61) (Figure 2). Conclusions: Our study revealed increased mortality and complications in COVID-19 patients with AMI, highlighting significant racial disparities. Urgent measures addressing healthcare disparities, such as enhancing access and promoting culturally sensitive care, are needed to improve health equity.